The possibilities for a SPAC in the Icelandic market - Edda Ingibjörg Gunnarsdóttir 2000-; Pétur Melax 1998- (2022)
Our goal was to find out if Special Purpose Acquisition Companies, here after SPAC were possible in Iceland for Stoðir hf. NASDAQ Iceland introduced their new rules allowing for SPACs to be registered on the stock exchange. However, the reception of the idea is not as positive as one might think, especially comparing to the popularity of SPACs in the US. In this research qualitative research method is used to get a more in-depth findings. Pension funds who are one of the largest investors in Iceland would not focus on investing in SPACs because of the uncertainty revolving around it. However private and institutional investors are more likely to invest. Venture capital firms were split in their strategy with one seeing the possibility of an exit strategy and a way to raise funds while the other did not. Limited knowledge of SPACs as well as no SPAC having been set up in Iceland before might cause hesitation in investing. With Iceland being a small economy in terms of other countries on the Secondary Emerging Market list from FTSE the options of companies are limited as well. However, across the board, it was agreed that a well-respected sponsor is needed to lead the project. Key words: SPAC, stock market, Icelandic financial market, merger, acquisition, private company.